Developmental Exposure to Endocrine Disruptors Expands Murine Myometrial Stem Cell Compartment as a Prerequisite to Leiomyoma Tumorigenesis. (11th November 2016) - Mas, Aymara; Stone, Leyland; O'Connor, Paul M.; Yang, Qiwei; Kleven, Daniel; Simon, Carlos; Walker, Cheryl L.; Al‐Hendy, Ayman
Abstract : Despite the high prevalence and major negative impact of uterine fibroids (UFs) on women's health, their pathogenesis remains largely unknown. While tumor‐initiating cells have been previously isolated from UFs, the cell of origin for these tumors in normal myometrium has not been identified. We isolated cells with Stro1/CD44 surface markers from normal myometrium expressing stem cell markers Oct‐4/c‐kit/nanog that exhibited the properties of myometrial stem/progenitor‐like cells (MSCs). Using a murine model for UFs, we showed that the cervix was a hypoxic "niche" and primary site (96%) for fibroid development in these animals. The pool size of these MSCs also responded to environmental cues, contracting with age and expanding in response to developmental environmental exposures that promote fibroid development. Translating these findings to women, the number of MSCs in unaffected human myometrium correlated with risk for developing UFs. Caucasian (CC) women with fibroids had increased numbers of MSCs relative to CC women without fibroids, and African‐American (AA) women at highest risk for these tumors had the highest number of MSCs: AA‐with fibroids > CC‐with fibroids > AA‐without fibroids > CC‐without fibroids. These data identify Stro1 + /CD44 + MSCs as MSC/progenitor cell for UFs, and a target for ethnic and environmental factors that increase UF risk. Stem Cells 2017;35:666–678 Abstract : Early life exposure to environmental toxicants during the sensitive period of uterine development, expands the number of myometrial stem cells as well as permanently reprograms and attenuates key DNA damage repair gene capacity, leading to the development of uterine fibroids. This paradigm shifting concept provides translational implications of value to evaluate if real time quantification of the number of stem cells in a tissue, such as myometrium, could be a predictor of future tumor risk. Importantly, it presents a foundation for an individualized approach for stem cell based targeted therapy of tumors.